2006
DOI: 10.1111/j.1442-2018.2004.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐efficacy in Infant Care Scale: Development and psychometric testing

Abstract: The Self-Efficacy in Infant Care Scale (SICS) is a self-administered measure to assess maternal judgments about the ability to care for the baby during the first year of life. The SICS was initially composed of 67 items and was tested on 397 Thai mothers with infants < 12 months old. The test demonstrated adequate internal consistency and test-retest reliability. Factor analysis yielded 42 items with five dimensions of self-efficacy in infant care. With an acceptable model fit using confirmatory factor analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 13 publications
1
16
0
1
Order By: Relevance
“…Self-efficacy has been shown to directly affect the quality of care provided to the newborn (4). If a mother is not ready to accept the motherhood role or have doubts about the effectiveness of her parental role, the management is challenged and this feeling of inadequacy combined with the lack of clear understanding of herself and inability to create mechanisms to cope with these challenges may lead to postpartum depression (5).…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy has been shown to directly affect the quality of care provided to the newborn (4). If a mother is not ready to accept the motherhood role or have doubts about the effectiveness of her parental role, the management is challenged and this feeling of inadequacy combined with the lack of clear understanding of herself and inability to create mechanisms to cope with these challenges may lead to postpartum depression (5).…”
Section: Introductionmentioning
confidence: 99%
“…A literature review identified validated questionnaires on breastfeeding self-efficacy[18-21] and self-efficacy in infant care[23,24]. These were used to develop questions to assess mother's confidence (self-efficacy)[25] in infant growth monitoring and feeding so that her baby would not gain too much weight.…”
Section: Methodsmentioning
confidence: 99%
“…In broad terms, self‐efficacy takes into account how people think or feel, their level of commitment and their chosen course to achieve goals despite the challenges and difficulties they might face . In medicine, self‐efficacy has been associated with different aspects of general health; for example, adherence to diabetes treatment , decrease in the risk of coronary heart disease and better health‐related quality of life . Similarly, in dentistry, several studies found a positive relationship between self‐efficacy and tooth brushing and between self‐efficacy and dental health .…”
Section: Introductionmentioning
confidence: 99%